(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the success rates of end-to-side and side-to-side techniques of Arterio Venous fistula formation for end stage kidney diseases. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Department of Urology, PUMHS, Nawabshah from March 2014 to February 2016. Materials and Methods: Cases of end stage kidney diseases were selected from outdoor and referred cases from other health facilities on inclusion and exclusion criteria. All cases were randomly divided in two equal size groups A and B. In group A end to side technique was used and in group B side to side technique was used for arterio venous fistula (AVF) formation for hemodialysis in patients with end stage kidney diseases. All AVF was made surgically under local anesthesia at non dominant upper limb near the wrist. Success of each technique was established by determining the postoperative patency of AVF in terms of palpable thrill and flow of blood with the help of Doppler ultrasound. Data was analyzed and success rate of each technique was calculated and any difference in the results of both techniques was noted. Results: Mean age of the patients was 44 years, SD± 7 and a range of 19 to75 years. Male to female ratio was 5:3. In group A out of 45 cases of end to side fistula, 38 cases were found patent showing a success rate of 84%. In group B out of 45 case of side to side fistula, 36 cases were found patent showing a success rate of 80%. Conclusion: The success rates of end to side and side to side technique of AVF are 84% and 80% respectively, reflecting no great difference between the results of these two techniques of arterio venus fistula formation for end stage kidney diseases.